Plasma metabolic profiling after cortical spreading depression in a transgenic mouse model of hemiplegic migraine by capillary electrophoresis – mass spectrometry1. Issue 5 (21st May 2015) - Shyti, Reinald; Kohler, Isabelle; Schoenmaker, Bart; Derks, Rico J. E.; Ferrari, Michel D.; Tolner, Else A.; Mayboroda, Oleg A.; van den Maagdenberg, Arn M. J. M.
<x xml:space="preserve">Abstract</x> Cortical spreading depression-induced brain metabolic changes have been captured in the plasma of a transgenic migraine mouse model using CE-MS.